Preparation method and application of nickel hydroxide / ferrocobalt alloy nanosheet electrocatalyst

The morphology of cobalt ferroalloy is improved by the nickel nitrate corrosion method, and nickel hydroxide/cobalt ferroalloy nanosheet electrocatalyst is prepared, which solves the problems of easy agglomeration, low activity and poor stability of cobalt ferroalloy catalysts, and achieves high-efficiency and low-cost electrolytic water Hydrogen production catalyst has broad industrial application prospects.

CN119162605AActive Publication Date: 2024-12-20SHIHEZI UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411302593.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing cobalt ferroalloy catalysts are prone to agglomeration, have low catalytic activity, poor stability, complex preparation process and high cost, which limits their industrial application in the field of electrolytic hydrogen production.

Method used

The morphology of cobalt ferroalloy is improved by nickel nitrate corrosion method, cobalt ferroalloy is grown on the foam nickel surface by electrochemical deposition, and electrochemical corrosion is carried out in nickel nitrate solution to form nickel hydroxide/cobalt ferroalloy nanosheet electrocatalyst to enhance the catalyst mechanical strength and stability.

Benefits of technology

The OER activity and stability of the catalyst are significantly improved, the reaction kinetic resistance is reduced, and the long-term high-efficiency performance is achieved under industrial-grade flow density. The preparation method is low in cost and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048102100000121
    Figure BDA0005048102100000121
  • Figure BDA0005048102100000122
    Figure BDA0005048102100000122
  • Figure BDA0005048102100000131
    Figure BDA0005048102100000131
Patent Text Reader

Abstract

The invention provides a preparation method and application of a nickel hydroxide / ferrocobalt alloy nanosheet electrocatalyst. The method comprises the following steps: dissolving FeSO4. 7H2O, CoSO4. 7H2O, NH4H2PO4 and Na3 (C6H5O7). 2H2O in deionized water to form a mixed solution; carrying out constant-current cathode deposition for a certain time by taking the foamed nickel as a working electrode and the mixed solution as an electrochemical deposition solution; and washing the obtained sample with deionized water, and drying to obtain the cobalt-iron alloy electrocatalyst. And placing the obtained cobalt-iron alloy electrocatalyst in a nickel nitrate solution, enabling the cobalt-iron alloy electrocatalyst to be uniformly corroded in the solution spontaneously, and washing and drying a sample after the cobalt-iron alloy electrocatalyst is corroded for a certain time to obtain the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst. The morphology, the catalytic activity and the oxygen evolution stability of the prepared catalyst are well improved. The nickel nitrate corrosion method provided by the invention has the advantages of low cost, low energy consumption, easiness in large-scale production and the like, has universality in the aspect of preparing an excellent transition metal OER catalyst, and shows a huge industrial application prospect in the field of hydrogen production by electrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy conversion, and specifically relates to a preparation method and application of a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst. Background Art

[0002] With the impending depletion of fossil energy and the increasingly severe environmental pollution problem, the world today faces the dual challenges of energy transformation and solving environmental problems. As an energy carrier, hydrogen has the advantages of high energy density, clean and pollution-free, and wide application, and is considered to be the most promising alternative to fossil energy. At present, among the many hydrogen production technologies, water electrolysis hydrogen production technology driven by renewable energy such as solar energy and wind energy is highly favored due to its simplicity, high efficiency and easy industrial application. Water electrolysis hydrogen production is divided into two half reactions: oxygen evolution reaction (OER) at the anode and hydrogen evolution reaction (HER) at the cathode. However, since OER is accompanied by the coupled transfer of four electrons and protons, the reaction energy barrier is high and the kinetics are slow, which becomes a bottleneck for efficient water electrolysis hydrogen production, seriously restricting the efficiency of water electrolysis hydrogen production.

[0003] Developing cost-effective, high-performance electrocatalysts that can operate stably for a long time under harsh conditions to reduce the energy barrier in the OER process and improve the reaction kinetics remains the key to improving the energy conversion efficiency in the industrial water electrolysis process. However, the platinum group metal electrocatalysts (such as IrO2 and RuO2) with excellent electrocatalytic activity are severely hampered in their industrial application in the field of water electrolysis due to their scarcity in the earth's crust, high prices, and easy deactivation in alkaline media. Therefore, it is still a very arduous challenge to develop inexpensive, highly catalytically active and stable non-precious metal electrocatalysts to reduce the energy barrier of OER, improve reaction kinetics, and improve the energy conversion efficiency in the water electrolysis process.

[0004] In order to solve the above problems, researchers have developed a large number of non-precious metal catalysts such as alloys, oxides, hydroxides, oxyhydroxides, phosphides, sulfides, nitrides, carbides and metal organic frameworks (MOFs). Among these electrocatalysts, alloys, especially cobalt-iron alloys, have excellent conductivity and fast charge transfer capabilities during electrocatalysis, and are a class of excellent OER catalysts. However, due to the limitations of cobalt-iron alloys themselves, that is, cobalt-iron alloys are prone to reduce the overall surface energy by agglomeration, which is very unfavorable for the OER process, because this agglomeration phenomenon easily leads to a decrease in the number of surface catalytic active sites of cobalt-iron alloy catalysts, which is not conducive to the occurrence of OER. On the other hand, agglomerates are not conducive to the transfer of charge and mass and the rapid diffusion of oxygen bubbles during the OER process, resulting in relatively slow OER kinetics. In addition, the traditional synthesis methods of cobalt-iron alloy catalysts (such as coprecipitation, sol-gel, chemical vapor deposition and hydrothermal synthesis) are complicated, costly and not conducive to large-scale production. These factors cannot be ignored when preparing Co-Fe alloy OER catalysts. Only by fully considering these factors and solving these problems can the industrial production and application of Co-Fe alloy water electrolysis hydrogen production catalysts be realized. Generally speaking, the construction of ultrathin nanosheet electrocatalysts can significantly shorten the charge / mass transfer path and reduce the transfer resistance during the OER process, while accelerating the diffusion rate of oxygen bubbles, thereby accelerating the OER reaction kinetics. However, choosing a simple method to synthesize Co-Fe alloy catalysts, especially developing effective strategies to regulate their morphology (such as constructing nanosheets) to prevent agglomeration, increase surface area, increase the number of OER active sites and enhance structural stability, is still a major challenge for achieving long-term and efficient OER performance at industrial current density.

[0005] Aiming at the limitations of the cobalt-iron alloy catalyst in the prior art, such as easy agglomeration, low catalytic activity, poor stability, complex preparation process, high cost and difficulty in large-scale production and application, the present invention proposes a simple, cost-effective and easy-to-scale nickel nitrate corrosion method to improve the morphology of the cobalt-iron alloy catalyst, thereby improving its electrocatalytic activity and stability. The performance attenuation of the prepared catalyst after long-term OER testing at industrial-grade flow density is basically negligible. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst, and the morphology, catalytic activity and stability of the cobalt-iron alloy electrocatalyst are improved by a nickel nitrate corrosion method. The cobalt-iron alloy is in-situ grown on the surface of nickel foam by an electrochemical deposition method, and then the cobalt-iron alloy is placed in a nickel nitrate solution of a certain concentration and temperature for electrochemical corrosion. The inherent characteristics that the cobalt-iron alloy is prone to electrochemical corrosion in a humid environment and iron is more easily corroded are mainly utilized to transform this harmful electrochemical corrosion behavior into an effective strategy for preparing a catalyst, and the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst is successfully prepared. The uniform corrosion of iron on the surface of the cobalt-iron alloy provides a necessary place for the uniform growth of nickel hydroxide, and the in-situ grown nickel hydroxide layer acts as a protective film to effectively prevent further corrosion of iron. This interaction greatly enhances the mechanical strength of the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst, thereby giving the catalyst excellent stability under harsh conditions.

[0007] On the other hand, during the corrosion process, the formation of nanosheets not only significantly shortens the transfer path of charge and mass in the OER process, but also reduces the resistance in the transfer process. These structural optimizations work together to make the catalyst show faster reaction kinetics, thereby achieving a significant improvement in OER catalytic activity and stability. The nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst was directly used as the working electrode for the OER reaction, and the OER performance was tested in an alkaline medium. The results showed that compared with the cobalt-iron alloy catalyst, the catalyst not only showed excellent OER activity, but also showed excellent OER performance at 1200 mA cm -2 It has excellent stability under current density, and there is basically no performance attenuation after 120h of stability test. In addition, the nickel nitrate corrosion method proposed in the present invention is used to modify metal organic frameworks (MOFs), metal sulfides and metal phosphides electrocatalysts, and the morphology, catalytic activity and stability of the prepared catalysts are well improved. Compared with the preparation method of traditional OER catalysts, the nickel nitrate corrosion method proposed in the present invention has the advantages of low cost, low energy consumption, easy large-scale production, wide application range, etc., and this method is universal in the preparation of excellent transition metal OER catalysts, showing great industrial application prospects in the field of water electrolysis hydrogen production.

[0008] Another object of the present invention is to provide an application of a nickel hydroxide / cobalt-iron alloy nano-electrocatalyst in the field of electrocatalysis.

[0009] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0010] The method for preparing a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst of the present invention comprises the following steps:

[0011] S1, dissolve FeSO4·7H2O, CoSO4·7H2O, NH4H2PO4 and Na3(C6H5O7)·2H2O in deionized water to form a mixed solution;

[0012] S2, using the washed and dried nickel foam as a working electrode, and using the solution in step S1 as an electrochemical deposition solution to perform constant current cathode deposition for a certain period of time; then washing the obtained sample with deionized water, and drying it to obtain a cobalt-iron alloy electrocatalyst;

[0013] S3, placing the cobalt-iron alloy electrocatalyst obtained in step S2 in a nickel nitrate solution of a certain concentration and temperature, and utilizing the characteristic of iron being susceptible to electrochemical corrosion to cause it to spontaneously and uniformly corrode in the solution. After a certain period of corrosion, the sample is washed and dried to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

[0014] In step S1 of the present invention, the molar number of FeSO4·7H2O is 1.0-4.0 mmol, the molar number of CoSO4·7H2O is 0.2-2.5 mmol, the molar number of NH4H2PO4 is 1.0-5.0 mmol, the molar number of Na3(C6H5O7)·2H2O is 1.0-3.0 mmol, and the volume of deionized water is 50 mL.

[0015] The electrochemical deposition time of the present invention is 600-3600s.

[0016] Preferably, the electrochemical deposition time of the present invention is 1800s.

[0017] The constant current cathode deposition current density of the present invention is -60mA / cm 2 .

[0018] The concentration of the nickel nitrate solution of the present invention is 0.02-0.12 mol / L.

[0019] Preferably, the concentration of the nickel nitrate solution of the present invention is 0.10 mol / L.

[0020] The corrosion time of the cobalt-iron alloy electrocatalyst in the nickel nitrate solution is 6-48 hours.

[0021] Preferably, the corrosion time of the cobalt-iron alloy electrocatalyst of the present invention in the nickel nitrate solution is 12 hours.

[0022] The corrosion temperature of the cobalt-iron alloy electrocatalyst in the nickel nitrate solution is 25-55°C.

[0023] Preferably, the corrosion temperature of the cobalt-iron alloy electrocatalyst of the present invention in the nickel nitrate solution is 45°C.

[0024] The nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst prepared by the method for preparing the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst of the present invention is applied in the field of electrocatalysis.

[0025] The nickel nitrate corrosion method used in the preparation method of the present invention can also be used for modifying metal organic frameworks (MOFs), metal sulfides and metal phosphides in electrocatalysts.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The morphology of the electrocatalyst prepared by the present invention presents a staggered 3D porous nanosheet structure, which is not only conducive to full contact with the electrolyte solution, but also conducive to reducing the charge / mass transmission resistance during the OER reaction, accelerating the diffusion of oxygen bubbles, and thus accelerating the OER reaction kinetics. In addition, the staggered nanosheet structure makes the catalyst have a stable structure.

[0028] 2. In the preparation method of the present invention, the uniform corrosion of iron on the surface of the cobalt-iron alloy provides a necessary place for the uniform growth of nickel hydroxide, and the in-situ grown nickel hydroxide layer acts as a protective film, effectively preventing further corrosion of iron. This interaction greatly enhances the mechanical strength of the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst, thereby giving the catalyst excellent stability under harsh conditions.

[0029] 3. In the present invention, during the corrosion process, the formation of nanosheets not only significantly shortens the transfer path of charge and mass in the OER process, but also reduces the resistance in the transfer process. These structural optimizations work together to enable the catalyst to exhibit more rapid reaction kinetics, thereby achieving significant improvements in catalytic activity and stability. See Table 1. The nickel hydroxide / cobalt-iron alloy electrocatalyst prepared in Example 2 exhibits excellent OER activity and stability, and can provide 10 mA cm with an overpotential of only 193 mV. -2 The current density and overpotential of 313 mV can provide 1200 mA cm -2 After 120 hours of stability testing, the industrial current density only decreased by 32 mA cm -2 However, a single CoFe alloy electrocatalyst requires an overpotential as high as 274 mV to deliver 10 mA cm -2 The current density and overpotential of 445 mV can provide 1200 mA cm -2 The industrial-grade current density was reached, and the stability showed obvious attenuation within 20 hours. The above results fully demonstrate that the nickel hydroxide / cobalt-iron alloy electrocatalyst prepared by the present invention has excellent OER activity and stability, and has great industrial application prospects.

[0030] 4. In the OER performance of the electrocatalysts prepared in Example 2 and Comparative Examples 1 to 3 of the present invention, the nickel hydroxide / cobalt-iron alloy electrocatalyst prepared in Example 2 (10 mA cm -2 Overpotential: 193mV, Tafel slope: 13.9mVdec -1 ; Charge transfer resistance: 0.26Ω) Comparison Example 1 (10mA cm -2 Overpotential: 274mV, Tafel slope: 37.1mVdec -1 ; Charge transfer resistance: 1.42Ω), Comparative Example 2 (10mA cm -2 Overpotential: 213mV, Tafel slope: 25.9mVdec -1 ; Charge transfer resistance: 0.39Ω) and Comparative Example 3 (10mA cm -2 Overpotential: 261mV, Tafel slope: 37.9mVdec -1 ; Charge transfer resistance: 0.78Ω) The prepared electrocatalyst has lower overpotential, Tafel slope and charge transfer resistance. In addition, when one of the metal elements nickel, cobalt or iron is missing in the electrocatalyst, the OER performance of the electrocatalyst is reduced, indicating that nickel, cobalt and iron have obvious synergistic effects in improving the OER performance of the electrocatalyst.

[0031] 5. The nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst prepared by the preparation method of the present invention is directly used as a working electrode for OER reaction. The OER performance test is carried out in an alkaline medium. The results show that compared with the cobalt-iron alloy catalyst, the catalyst not only exhibits excellent OER activity, but also has a high OER performance at 1200 mA cm -2 It has excellent stability under different current densities, and there is basically no performance attenuation after 120 hours of stability testing.

[0032] 6. The nickel nitrate corrosion method proposed in the present invention can also be used to modify metal organic frameworks (MOFs), metal sulfides and metal phosphides electrocatalysts, and the morphology, catalytic activity and stability of the prepared catalysts are well improved. Compared with the preparation method of traditional OER catalysts, the nickel nitrate corrosion method proposed in the present invention has the advantages of low cost, low energy consumption, easy large-scale production, and a wide range of applications. Moreover, this method is versatile in preparing excellent transition metal OER catalysts, and has shown great industrial application prospects in the field of water electrolysis for hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 :Preparation flow chart of nickel hydroxide / cobalt iron alloy nanosheet electrocatalyst;

[0034] Figure 2 : SEM image of the nickel hydroxide / cobalt-iron alloy nanosheets prepared in Example 2;

[0035] Figure 3 : SEM image of the cobalt-iron alloy prepared in Comparative Example 1;

[0036] Figure 4 : SEM image of iron / nickel foam corroded by nickel nitrate solution prepared in Comparative Example 2;

[0037] Figure 5 : SEM image of cobalt / nickel foam corroded by nickel nitrate solution prepared in Comparative Example 3;

[0038] Figure 6 : OER polarization curves of nickel hydroxide / cobalt-iron alloy nanosheet electrocatalysts prepared in Examples 1 to 5;

[0039] Figure 7 : Overpotential diagrams required for the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalysts prepared in Examples 1 to 5 to drive the OER reaction at different current densities;

[0040] Figure 8 : The nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst prepared in Example 2 and the cobalt-iron alloy prepared in Comparative Example 1 were -2 OER reaction stability test curve at current density;

[0041] Fig. 9 : OER reaction polarization curves of the electrocatalysts prepared in Example 2 and Comparative Examples 1 to 3;

[0042] Fig.10 : Electrochemical impedance spectra of OER reactions of the electrocatalysts prepared in Example 2 and Comparative Examples 1 to 3;

[0043] Fig.11 :NiNO3 corrosion method improves the morphology of FeOOH-MOF and promotes OER reaction activity and stability Figure: a) SEM image of FeOOH-MOF; b) SEM of FeOOH-MOF after NiNO3 corrosion; c) OER reaction polarization curve of electrocatalyst; d) FeOOH-MOF and FeOOH-MOF after NiNO3 corrosion at 710 mA cm -2 OER reaction stability test curve under current density;

[0044] Fig.12 :Nitric Acid Nickel Corrosion Method Improves Fe 1-x The morphology of S promotes the activity and stability of OER reaction.1-x SEM image of S; b) Fe after nickel nitrate corrosion 1-x SEM of S; c) OER reaction polarization curve of electrocatalyst; d) Fe 1-x S at 1200mA·cm -2 OER reaction stability test curve under current density and Fe after nickel nitrate corrosion 1-x S at 1300mA·cm -2 OER reaction stability test curve under current density;

[0045] Fig.13 :NiNO3 corrosion method improves the morphology of FeP4 and promotes OER reaction activity and stability Figure: a) SEM image of FeP4; b) SEM of FeP4 after NiNO3 corrosion; c) OER reaction polarization curve of electrocatalyst; d) FeP4 and FeP4 after NiNO3 corrosion at 1258 mA cm -2 OER reaction stability test curve under current density. DETAILED DESCRIPTION

[0046] The following examples, comparative examples and extended application examples will further illustrate the present invention, but the contents of the present invention are not limited to these examples, comparative examples and extended application examples.

[0047] Example 1

[0048] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0049] Step 2: Dissolve 1.0mmol FeSO4·7H2O, 0.2mmol CoSO4·7H2O, 1.0mmol NH4H2PO4 and 1.0mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0050] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain a cobalt-iron alloy;

[0051] Step 4: Place the cobalt-iron alloy in 0.02 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 25°C for 6 hours, and the product was taken out, washed with deionized water and dried at 60°C to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

[0052] The preparation process flow chart of the nickel hydroxide / cobalt iron alloy nanosheet electrocatalyst is as follows: Figure 1 shown.

[0053] Example 2

[0054] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0055] Step 2: Dissolve 3.5mmol FeSO4·7H2O, 1.0mmol CoSO4·7H2O, 4.5mmol NH4H2PO4 and 2.5mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0056] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain a cobalt-iron alloy;

[0057] Step 4: Place the cobalt-iron alloy in 0.10 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 45°C for 12 hours, and the product was taken out, washed with deionized water and dried at 60°C to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

[0058] Example 3

[0059] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0060] Step 2: Dissolve 2.0mmol FeSO4·7H2O, 0.4mmol CoSO4·7H2O, 2.0mmol NH4H2PO4 and 2.0mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0061] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain a cobalt-iron alloy;

[0062] Step 4: Place the cobalt-iron alloy in 0.05 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 35°C for 24 hours, and the product was taken out, washed with deionized water and dried at 60°C to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

[0063] Example 4

[0064] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0065] Step 2: Dissolve 4.0mmol FeSO4·7H2O, 1.5mmol CoSO4·7H2O, 5.0mmol NH4H2PO4 and 3.0mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0066] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain a cobalt-iron alloy;

[0067] Step 4: Place the cobalt-iron alloy in 0.02 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 55°C for 48 hours, and the product was taken out, washed with deionized water and dried at 60°C to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

[0068] Example 5

[0069] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0070] Step 2: Dissolve 2.5mmol FeSO4·7H2O, 2.5mmol CoSO4·7H2O, 2.5mmol NH4H2PO4 and 2.5mmol Na3(C6H5O7)·2H2O in 50ml deionized water at room temperature and stir evenly;

[0071] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain a cobalt-iron alloy;

[0072] Step 4: Place the cobalt-iron alloy in 0.12 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 25°C for 36 hours, and the product was taken out, washed with deionized water and dried at 60°C to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

[0073] For the above Examples 1-5, since the standard potential of the iron electrode pair (Fe 2+ / Fe:-0.447V) is less than the standard potential of the cobalt electrode pair (Co 2+ / Co:-0.280V), in the cobalt-iron alloy, iron is more susceptible to electrochemical corrosion.

[0074] Nickel nitrate solution is neutral and slightly acidic (pH = 6-7). Nitrate ions are easily reduced at the cathode of electrochemical corrosion, and iron is oxidized at the anode. The electrochemical corrosion process follows the following principles:

[0075] Anode: Fe(s)=Fe 2+ (aq)+2e -

[0076] Cathode: H2O(l)+NO3 - (aq)+2e - =2OH - (aq)+NO2- (aq)

[0077] Overall reaction: Fe(s)+NO3 - (aq)+H2O(l)=Fe 2+ (aq)+2OH - +NO2 - (aq).

[0078] Since Ksp Ni(OH)2 / Ksp Fe(OH)2 =40.0, the order of Fe(OH)2 and Ni(OH)2 precipitation is no longer determined by the size of the precipitate Ksp, but by the concentration of the metal cations. 2+ The concentration is relatively high (0.02-0.12 mol·L -1 ), so Ni(OH)2 precipitation is produced preferentially, and the principle is as follows:

[0079] Ni 2+ (aq)+2OH - (aq) = Ni(OH)2(s).

[0080] The uniform corrosion of iron and the in-situ growth of nickel hydroxide form a nanosheet structure. The formation of nanosheets effectively increases the contact area between the electrocatalyst and the electrolyte, thereby improving the utilization of the catalyst active sites. On the other hand, the ultrathin nanosheets are conducive to the rapid transfer of charge / mass and the rapid diffusion of bubbles during the electrocatalytic process, thus giving the catalyst excellent OER performance.

[0081] Comparative Example 1

[0082] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0083] Step 2: Dissolve 3.5mmol FeSO4·7H2O, 1.0mmol CoSO4·7H2O, 4.5mmol NH4H2PO4 and 2.5mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0084] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm-2 The sample was taken out, washed with deionized water and dried at 60°C to obtain a cobalt-iron alloy.

[0085] Comparative Example 2

[0086] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0087] Step 2: Dissolve 3.5mmol FeSO4·7H2O, 4.5mmol NH4H2PO4 and 2.5mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0088] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain iron / nickel foam;

[0089] Step 4: Place iron / nickel foam in 0.10 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 45°C for 12 hours, and the catalyst was taken out, washed with deionized water and dried at 60°C to obtain an iron / nickel foam electrocatalyst corroded by the nickel nitrate solution.

[0090] Comparative Example 3

[0091] Step 1: Cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for later use;

[0092] Step 2: Dissolve 1.0mmol CoSO4·7H2O, 4.5mmol NH4H2PO4 and 2.5mmol Na3(C6H5O7)·2H2O in 50mL deionized water at room temperature and stir evenly;

[0093] Step 3: Use the washed and dried nickel foam as the working electrode and immerse it in the above solution. The effective geometric area of ​​the working electrode is 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out and washed with deionized water and dried at 60°C to obtain cobalt / nickel foam;

[0094] Step 4: Place cobalt / nickel foam in 0.10 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at 45°C for 12 hours, and the catalyst was taken out, washed with deionized water and dried at 60°C to obtain a cobalt / nickel foam electrocatalyst corroded by the nickel nitrate solution.

[0095] Extended application example 1

[0096] Step 1: Synthesize FeOOH-MOF by solvothermal method; First, cut the nickel foam into 1×2 cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 Hydrochloric acid, deionized water and 95% ethanol were ultrasonically washed for 5 minutes to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for use; then 0.375mmol FeCl2·4H2O and 0.2mmol terephthalic acid were dissolved in 10mL N,N-dimethylformamide, 1mL ethanol and 1mL deionized water, stirred until completely dissolved, and then transferred to a 20mL polytetrafluoroethylene-lined reactor, and the washed nickel foam was placed in the reactor containing the solution and reacted at 120°C for 3h; finally, the obtained product was washed alternately with ethanol and deionized water three times and dried at 60°C for 8h to obtain FeOOH-MOF.

[0097] Step 2: Place FeOOH-MOF in 0.10 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at room temperature for 12 hours, and the FeOOH-MOF electrocatalyst was obtained after being taken out, washed with deionized water and dried at 60°C.

[0098] Extended application example 2

[0099] Step 1: Synthesis of Fe by electrodeposition 1-x S; First, cut the nickel foam into 1×2cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for use. Then 3.5mmol FeSO4·7H2O, 2.5mmol Na3(C6H5O7)·2H2O, 4.5mmol NH4H2PO4 and 2.5mmol Na2S·9H2O were dissolved in 50.0mL deionized water as an electrodeposition solution for use. Then the washed and dried nickel foam was used as a working electrode and immersed in the above solution. The effective geometric area of ​​the working electrode was 1cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60 °C to obtain Fe 1-x S.

[0100] Step 2: Fe 1-x S was set at 0.10 mol·L -1 The nickel nitrate solution was used for corrosion reaction at room temperature for 12 hours. After being taken out, it was washed with deionized water and dried at 60°C to obtain Fe 1-x S electrocatalyst.

[0101] Extended application example 3

[0102] Step 1: Synthesize FeP4 by electrodeposition; First, cut the nickel foam into 1×2 cm 2 , the effective geometric area is 1cm 2 , respectively, using 1.0 mol·L -1 The nickel foam was ultrasonically washed with hydrochloric acid, deionized water and 95% ethanol for 5 min to remove oxides and impurities on the surface of the nickel foam, and then dried at 60°C for use. Then 3.5 mmol FeSO4·7H2O and 9.5 mmol NaH2PO2·H2O were dissolved in 50.0 mL deionized water as an electrodeposition solution. The washed and dried nickel foam was used as a working electrode and immersed in the above solution. The effective geometric area of ​​the working electrode was 1 cm 2 , silver / silver chloride and platinum sheet were used as reference electrode and counter electrode respectively; at -60 mA·cm -2 The sample was taken out, washed with deionized water and dried at 60°C to obtain FeP4.

[0103] Step 2: Place FeP4 in 0.10 mol·L -1 The nickel nitrate solution was subjected to corrosion reaction at room temperature for 12 hours. After being taken out, it was washed with deionized water and dried at 60°C to obtain the FeP4 electrocatalyst after nickel nitrate corrosion.

[0104] SEM image of the electrocatalyst prepared from Example 2 ( Figure 2 ) It can be seen that the morphology of the catalyst presents a staggered 3D porous nanosheet structure, which is not only conducive to full contact with the electrolyte solution, but also conducive to reducing the charge / mass transfer resistance during the OER reaction, accelerating the diffusion of oxygen bubbles, and thus accelerating the OER reaction kinetics. In addition, the staggered nanosheet structure makes the catalyst have a stable structure. However, from Comparative Example 1 ( Figure 3 ), Comparative Example 2( Figure 4 ) and Comparative Example 3 ( Figure 5 ) The SEM image of the catalyst prepared by ) shows that the catalyst basically does not have a staggered nanosheet structure, and such a catalyst often has the limitations of unsatisfactory catalytic activity and unstable structure. The SEM image results show that the morphology and structure of the catalyst can only be well improved when the three metal elements of nickel, cobalt and iron are present at the same time.

[0105] Test Example 1 Electrochemical OER property test:

[0106] The present invention uses the electrocatalysts prepared by the preparation methods of Examples 1 to 5, Comparative Examples 1 to 3 and Extended Application Examples 1 to Extended Application Example 3 directly as working electrodes for electrochemical OER reactions, and uses graphite rods and calibrated mercury / mercuric oxide as counter electrodes and reference electrodes, respectively, to perform electrochemical property tests on a Shanghai Chenhua electrochemical workstation;

[0107] Results: From Figure 6 , Figure 7 , Figure 8 As can be seen from Table 1, the nickel hydroxide / cobalt iron alloy electrocatalysts prepared in Examples 1 to 5, especially Example 2, show excellent OER activity and stability, and can provide 10 mA cm-2 at an overpotential of only 193 mV. -2 The current density and overpotential of 313 mV can provide 1200 mA cm -2 After 120 hours of stability testing, the industrial current density only decreased by 32 mA cm -2 However, a single CoFe alloy electrocatalyst requires an overpotential as high as 274 mV to deliver 10 mA cm -2 The current density and overpotential of 445 mV can provide 1200 mA cm -2 The industrial-grade current density was reached, and the stability showed obvious attenuation within 20 hours. The above results fully demonstrate that the nickel hydroxide / cobalt-iron alloy electrocatalyst prepared by the present invention has excellent OER activity and stability, and has great industrial application prospects.

[0108] Table 1

[0109]

[0110] from Fig. 9 , Fig.10 As can be seen from Table 2, among the OER performances of the electrocatalysts prepared in Example 2 and Comparative Examples 1 to 3 of the present invention, the nickel hydroxide / cobalt-iron alloy electrocatalyst prepared in Example 2 (10 mA cm -2 Overpotential: 193mV, Tafel slope: 13.9mV dec -1 ; Charge transfer resistance: 0.26Ω) Comparison Example 1 (10mA cm -2 Overpotential: 274mV, Tafel slope: 37.1mV dec -1 ; Charge transfer resistance: 1.42Ω), Comparative Example 2 (10mA cm -2 Overpotential: 213mV, Tafel slope: 25.9mV dec -1 ; Charge transfer resistance: 0.39Ω) and Comparative Example 3 (10mA cm -2 Overpotential: 261mV, Tafel slope: 37.9mV dec -1 ; Charge transfer resistance: 0.78Ω) The prepared electrocatalyst has lower overpotential, Tafel slope and charge transfer resistance. In addition, when one of the metal elements nickel, cobalt or iron is missing in the electrocatalyst, the OER performance of the electrocatalyst is reduced, indicating that nickel, cobalt and iron have obvious synergistic effects in improving the OER performance of the electrocatalyst.

[0111] Table 2

[0112]

[0113]

[0114] from Fig.11 It can be seen that after being corroded by nickel nitrate, the morphology and structure of the FeOOH-MOF catalyst are significantly improved; and the FeOOH-MOF after being corroded by nickel nitrate has the lowest OER onset potential and overpotential. In addition, compared with FeOOH-MOF, the FeOOH-MOF after being corroded by nickel nitrate has excellent OER stability, with a peak at 710 mA cm -2 After running for 120 h at a current density of , there was no obvious performance attenuation. This result shows that nickel nitrate corrosion can significantly improve the morphology and structure of FeOOH-MOF, thereby improving the OER reaction activity and stability of the catalyst.

[0115] from Fig.12 It can be seen that after nickel nitrate corrosion, Fe 1-x The morphology and structure of the S catalyst were significantly improved; and the Fe 1-x S has the lowest OER onset potential and overpotential. In addition, Fe 1-x S exhibits excellent OER stability at 1300 mA cm -2 After running for 120h at a current density of 1.54 W, the performance showed no obvious attenuation, while Fe 1-x S at 1200mA cm -2 The stability at the current density of 2.500 W / m was significantly reduced within 20 h. This result shows that the nickel nitrate corrosion method can significantly improve the Fe 1-x The morphology and structure of S can improve the OER reaction activity and stability of the catalyst.

[0116] from Fig.13 It can be seen that after being corroded by nickel nitrate, the morphology and structure of the FeP4 catalyst are significantly improved; and the FeP4 corroded by nickel nitrate has the lowest OER onset potential and overpotential. In addition, the FeP4 corroded by nickel nitrate has excellent OER stability, with a -2 After running for 120 h at a current density of 1258 mA cm -2 The stability of FeP4 at high current density showed a significant decay within 20 hours. This result shows that nickel nitrate corrosion can significantly improve the morphology and structure of FeP4, thereby improving the OER reaction activity and stability of the catalyst.

[0117] The above are only several implementation cases, comparative cases and extended application cases of the present invention, and do not limit the present invention in any form. Although the present invention has been disclosed as above with preferred implementation cases, comparative cases and extended application cases, the above is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent implementation cases of equivalent changes using the structure and technical content disclosed above without departing from the technical scope of the present invention. However, any simple modifications, equivalent changes and modifications made to the above implementation cases based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst, characterized in that: The steps include: S1, dissolve FeSO4·7H2O, CoSO4·7H2O, NH4H2PO4 and Na3(C6H5O7)·2H2O in deionized water to form a mixed solution; S2, using the washed and dried nickel foam as a working electrode, and using the solution in step S1 as an electrochemical deposition solution to perform constant current cathode deposition for a certain period of time; then washing the obtained sample with deionized water, and drying it to obtain a cobalt-iron alloy electrocatalyst; S3, placing the cobalt-iron alloy electrocatalyst obtained in step S2 in a nickel nitrate solution of a certain concentration, utilizing the characteristic of iron being susceptible to electrochemical corrosion to cause it to spontaneously and uniformly corrode in a solution of a certain temperature, and after a certain period of corrosion, washing and drying the sample to obtain a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst.

2. The preparation method according to claim 1, characterized in that: In step S1, the molar number of FeSO4·7H2O is 1.0-4.0 mmol, the molar number of CoSO4·7H2O is 0.2-2.5 mmol, the molar number of NH4H2PO4 is 1.0-5.0 mmol, the molar number of Na3(C6H5O7)·2H2O is 1.0-3.0 mmol, and the volume of deionized water is 50 mL.

3. The preparation method according to claim 1, characterized in that: The electrochemical deposition time in step S2 is 600-3600s, and the constant current cathode deposition current density is -60mA / cm 2 .

4. The preparation method according to claim 3, characterized in that: The electrochemical deposition time in step S2 is 1800 s.

5. The preparation method according to claim 1, characterized in that: The concentration of the nickel nitrate solution in step S3 is 0.02-0.12 mol / L.

6. The preparation method according to claim 5, characterized in that: The concentration of the nickel nitrate solution in step S3 is 0.10 mol / L.

7. The preparation method according to claim 1, characterized in that: In step S3, the corrosion time of the cobalt-iron alloy electrocatalyst in the nickel nitrate solution is 6-48 hours, and the corrosion temperature is 25-55°C.

8. The preparation method according to claim 7, characterized in that: In step S3, the corrosion time of the cobalt-iron alloy electrocatalyst in the nickel nitrate solution is 12 hours, and the corrosion temperature is 45°C.

9. A method for preparing a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst as claimed in claim 1 and application of the nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst prepared therefrom in the field of electrocatalysis.

10. Use of the preparation method of a nickel hydroxide / cobalt-iron alloy nanosheet electrocatalyst as claimed in claim 1 in modifying metal organic frameworks (MOFs), metal sulfides and metal phosphides electrocatalysts.

Citation Information

Patent Citations

  • Nickel-based layered double hydroxide nanosheet as well as room-temperature rapid green preparation method and application thereof

    CN111097423A

  • NF-NiFeOx(OH)y-S electrode as well as preparation and application thereof as OER catalytic material

    CN112575348A

  • Manchuronol sulfide electrocatalyst with high catalytic activity and stability, preparation method of Manchuronol sulfide electrocatalyst and application of Manchuronol sulfide electrocatalyst in electrolyzed water

    CN114525539A

  • Method for producing green hydrogen through coupling of magnetic field enhanced electro-catalysis biomass oxidation

    CN116121796A

  • FeOOH / S electrolyzed water catalyst and preparation method thereof

    CN117265583A